# For each of the differential equations in question, find the particular solution satisfying the given condition:(x + y)dy + (x – y) dx = 0; y = 1 when x = 1

(x + y)dy + (x - y)dx = 0

Here, putting x= kx and y = ky

= k0.f(x,y)

Therefore, the given differential equation is homogeneous.

(x + y)dy + (x - y)dx = 0

To solve it we make the substitution.

y = vx

Differentiating eq. with respect to x, we get

Integrating both sides, we get

y = 1 when x = 1

The required solution of the differential equation.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive Quiz on DIfferential Calculus50 mins
Interactive Quiz on Differential Calculus | Check Yourself56 mins
Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses